COMPOSITION AND CHARACTERISTICS OF RED MUD: A CASE STUDY ON TAYAN BAUXITE RESIDUE FROM ALUMINA PROCESSING PLANT AT WEST KALIMANTAN - Retno Damayanti; Herni Khareunissa (Indonesian Mining Journal, 2016)
Bauxite residue emerges as the major waste material during production of alumina from bauxite by the Bayer’s process. An alumina refinery built in Tayan, West Kalimantan has a production capacity of 300 thousand tons per year. It means that it will produce red mud or bauxite residue approximately 300 – 350 thousand tons per year and washing residue around 200 thousand tons per year. Right now, it is stored in a nearby disposal area. This paper focuses on the characteristic study of the bauxite residue to evaluate the potential pollution risk to the surrounding environment. This experimental-based study is conducted to get appraisal and description of the residue regarding its utilization. Some characterization tests were conducted in the laboratory to find the properties of bauxite residue coupled with the previous study. It is found from the study that  bauxite residue shows radioactivity elements. It comprises of oxides of iron, titanium, aluminum and silica along with some other minor constituents in the form of heavy metals and rare earth elements. Hazardous elements such as As, Pb, Cr and Hg were found in bauxite residue samples. But, the toxicity test showed that bauxite residue samples were not classified as hazardous material. Some rare earth elements such as Ga, Ce, Sc, Pr, Gd, Tb etc., were also detected in the samples.